Historisitas Doktrin Konflik dan Integrasi Sosial dalam Al-Qur'an - Ach. Fajruddin Fatwa (AL-TAHRIR, 2011)
Academic findings show that there is a clear distinction between Muslims and Orientalists when they learn al-Qur'an on social conflict and integration. Muslims employ legal and theological perspective that results in normative doctrines. As an internal study, it claims superiority and excellence over non-Muslims studies. According to Muslim scholars, conflict and peace is inseparable. Conflict is a price to uplift peaceful agendas. On the contrary, orientalists who make use socio-historic approach expose the dominance of conflict doctrines in Al-Qur'an over its instruction about peace. Islam is a religion that legalizes violence in its spread. This article is an attempt to make a bridge between the two perspectives to uncover socio-theological facts which trigger the doctrine of war in Islam.